Wind resistant Design of Ngarai Sianok Bridge in Bukittinggi, West Sumatera - Indonesia. (2017) - Permata, Robby; Andika, Matza Gusto; Fariduzzaman,; Hakim, Nurul; Van Martino, Edward; Suhara,
Abstract: Ngarai Sianok Bridge is planned to cross the Sianok valley in Bukittinggi, West Sumatera Province, Indonesia. It will be a record breaking bridge in Indonesia in term of pier height. Its pair of 173.6 m tall pylon (elevation of deck is 123 m) are much taller than any bridges in Indonesia to date (2016). Another special feature of this bridge is the structural type: multi span cable-stayed bridge with 4 pylons and 3 main span of 170 m. The total length of the bridge is 685 m. This paper describes the wind resistant design process for the bridge: from design criteria and conceptual design to wind tunnel tests. Three wind tunnel tests were performed: static sectional test, full model test without terrain and full model test with terrain. Results from wind tunnel testing show that the design bridge is safe from flutter instability and vortex-induced vibration problem.